Abiotic and biotic drivers of biomass change in a Neotropical forest. (27th March 2017) - van der Sande, Masha T.; Peña‐Claros, Marielos; Ascarrunz, Nataly; Arets, Eric J. M. M.; Licona, Juan Carlos; Toledo, Marisol; Poorter, Lourens
Summary: Tropical forests play an important role in the global carbon cycle, but the drivers of net forest biomass change (i.e. net carbon sequestration) are poorly understood. Here, we evaluate how abiotic factors (soil conditions and disturbance) and biotic factors (forest structure, diversity and community trait composition) shape three important demographic processes (biomass recruitment, growth and mortality) and how these underlie net biomass change. To test this, we evaluated 9 years of biomass dynamics using 48 1‐ha plots in a Bolivian tropical moist forest, and measured for the most abundant species eight functional traits that are important for plant carbon gain and loss. Demographic processes were related to the abiotic and biotic factors using structural equation models. Variation in net biomass change across plots was mostly due to stand‐level mortality, but mortality itself could not be predicted at this scale. Contrary to expectations, we found that species richness and trait composition – which is an indicator for the mass‐ratio theory – had little effect on the demographic processes. Biomass recruitment (i.e. the biomass growth by recruiting trees) increased with higher resource availability (i.e. water and light) and with high species richness, probably because of increased resource use efficiency. Biomass growth of larger, established trees increased with higher sand content, which may facilitate root growth of larger trees to deeper soil layers. In sum, diversity and mass‐ratio are of limited importance for the productivity of this forest. Instead, in this moist tropical forest with a marked dry season, demographic processes are most strongly determined by soil texture, soil water availability and forest structure. Only by simultaneously evaluating multiple abiotic and biotic drivers of demographic processes, better insights can be gained into mechanisms playing a role in the carbon sequestration potential of tropical forests and natural systems in general. Abstract : We evaluate how abiotic and biotic factors shape biomass recruitment, growth and mortality, and how these processes underlie net biomass change in a tropical forest. Net biomass change is mainly driven by mortality, but mortality is poorly predicted by abiotic and biotic factors. Productivity is determined by soil texture, soil water availability and forest structure, and not by diversity and mass‐ratio.